LEGITIMASI IDENTITAS ADAT DALAM DINAMIKA POLITIK AGRARIA (STUDI KASUS LEMBAGA SWAPRAJA DI YOGYAKARTA) - Antoro, Kus Sri (BHUMI: Jurnal Agraria dan Pertanahan, 2018)
Post New Order era is marked by the rise of movements that, claiming on the behalf of the indigenous people, attempt to take over the indigenous rights related to agrarian resources, including the feudalistic self-governing institution (swapraja) in Yogyakarta. That the status and rights of both indigenous community (Adat) and self-governing institution have been strictly distinguished by agrarian laws, it does not mean that the laws fully operate in social domain. In reality, the existence of the dualistic agrarian politics is recognized although it finds no room for legal certainty. By tracing and comparing between official historical sources, this article is critically reviewing the issue of the dynamics on indigenous community positioning in agrarian politics in the former self-governing region of Yogyakarta, as well as further consequences of the implementation of agrarian special authority following the issuance of Law Number 13 of 2012. Keywords: indigenous community, self-governing institution, agrarian resources.